2008
DOI: 10.1111/j.1439-0531.2008.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Captive Breeding of Cheetahs in South Africa – 30 Years of Data from the de Wildt Cheetah and Wildlife Centre

Abstract: The de Wildt Cheetah and Wildlife Centre was established in 1971 and the first cheetah cubs were born in 1975. During the period 1975-2005, 242 litters were born with a total of 785 cubs. Mean cub survival from 1 to 12 months and greater than 12 months of age was 71.3 and 66.2%, respectively. The majority of losses (84.9%) occurred during the first month postpartum whereas only 15.1% deaths took place between 1 and 12 months of age. Females were first bred at an age of approximately 3 years, reached maximum re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…In our study, the types of fecal progestagens showed no distinct difference among early (1-15 days), mid-(30-60 days) and late pregnancy (75-90 days) and among individuals. These results indicate that our assay method is effective for moni- ,3,4,5,and 6, toring progestagen profiles during pregnancy.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In our study, the types of fecal progestagens showed no distinct difference among early (1-15 days), mid-(30-60 days) and late pregnancy (75-90 days) and among individuals. These results indicate that our assay method is effective for moni- ,3,4,5,and 6, toring progestagen profiles during pregnancy.…”
Section: Discussionmentioning
confidence: 61%
“…In our study, the types of fecal progestagens showed no distinct difference among early (1-15 days), mid-(30-60 days) and late pregnancy (75-90 days) and among individuals. These results indicate that our assay method is effective for moni- ,3,4,5,and 6, toring progestagen profiles during pregnancy.In conclusion, the fecal progestagen assay, as an indicator of 5α-reduced pregnanes, is effective for detecting pregnancy and monitoring pregnant luteal activity in cheetahs. Continuous noninvasive monitoring of reproductive endocrinology is important for reliable management and care through pregnancy and parturition.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Behavioural observations, clinical and laboratory methods are all reported for oestrous monitoring and defining the reproductive status of individual female cheetahs and lions [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been variously reported that captive breeding programs are typified by poor reproductive performance ascribed anecdotally to a plethora of causes including captive stress, lack of genetic diversity, poor husbandry conditions and seasonal climatic changes [3,4]. Asymmetric reproductive aging has been demonstrated in cheetahs similar to other captive populations of non-carnivore species such as elephants and rhinoceros where older captive females demonstrate irregular oestrous cycles or may cease cyclic activity [6,19,20].…”
Section: Introductionmentioning
confidence: 99%